A novel splicing pathogenic variant in COL1A1 causing osteogenesis imperfecta (OI) type I in a Chinese family. Issue 9 (25th June 2020) - Han, Yaxin; Wang, Dongming; Guo, Jinli; Xiong, Qiuhong; Li, Ping; Zhou, Yong‐An; Zhao, Bin
Abstract: Background: Osteogenesis imperfecta (OI), a rare autosomal inheritable disorder characterized by bone fragility and skeletal deformity, is caused by pathogenic variants in genes impairing the synthesis and processing of extracellular matrix protein collagen type I. With the use of next‐generation sequencing and panels approaches, an increasing number of OI patients can be confirmed and new pathogenic variants can be discovered. This study sought to identify pathogenic gene variants in a Chinese family with OI I. Methods: Whole‐exome sequencing was used to identify pathogenic variants in the proband, which is confirmed by Sanger sequencing and cosegregation analysis; MES, HSF, and Spliceman were used to analyze this splicing variant；qRT‐PCR was performed to identify the mRNA expression level of COL1A1 in patient peripheral blood samples; Minigene splicing assay was performed to mimic the splicing process of COL1A1 variants in vitro; Analysis of evolutionary conservation of amino acid residues and structure prediction of the mutant protein. Results: A novel splicing pathogenic variant (c.3814+1G>T) was identified in this OI family by using whole‐exome sequencing, Sanger sequencing, and cosegregation analysis. Sequencing of RT‐PCR products from the COL1A1 minigene variant reveals a 132‐nucleotide (nt) insertion exists at the junction between exons 48 and exon 49 of the COL1A1 cDNA. Splicing assay indicates that the mutated minigene produces an alternatively spliced transcript which may cause a frameshift resulting in early termination of protein expression. The molecular analysis suggested that the altered amino acid is located at the C‐terminus of type I procollagen. Conclusion: Our study reveals the pathogenesis of a novel COL1A1 splicing pathogenic variant c.3814+1G>T in a Chinese family with OI I. Abstract : We use Whole exome sequencing identify a novel splicing pathogenic variant in COL1A1 gene causing osteogenesis imperfecta (OI) type I in a Chinese family.